Kenosis: Solidaritas Perjumpaan dalam Relasi Kasih Trinitaris - Samuel Pella (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
Kenosis has a connection with the trinity. Even though kenosis is a free act of the Son, this does not mean that there is no trinitarian act in it. This relationship is clearly seen in the personal unity of the Father, Son, and Holy Spirit. The Son who emptied himself and became the same as humans, wants to show his obedience to the will of the Father who sent Him to save humans and His solidarity to humans. Each person meets out of love for one another. This loving relationship is clear proof that they are bound in one unity and cannot be separated. Kenosis becomes real because there is an encounter of solidarity that occurs in the relationship of trinitarian love. Encounters based on love enable a close unity in togetherness with others. Thus, kenosis is a path taken so that humans can be saved thanks to the Son in trinitarian action. The encounters that occur are always meaningful and have a huge effect. Trinitarian action can occur when each person gives space and allows themselves to be embraced by others. In the unity of love, the Trinity relates and with the spirit of perichoresis they meet one another.